Development of diagnosis directory and algorithm to facilitate physician diagnosis mapping with concepts in international classification of diseases - Paoin, Wansa (Journal of the Thai Medical Informatics Association, 2022)
The International Statistical Classification of Diseases and Related Health Problems 10th revision or ICD-10 is the classification of diseases system developed and maintained by the World Health Organization – WHO since 1946. The current edition is the 5th edition released in 2016[1]. Many countries in the world use ICD-10 as the coding system to capture diagnosis statement in the patient records and produce morbidity and mortality statistics and compare health situation among countries in the same region. Since 1994, Thailand used ICD-10 in all public hospitals to capture all diagnosis statements for every out-patient department (OPD) visits as well as every in-patient department (IPD) admission episodes. Since 2015, all individual patient data with ICD-10 codes from all public health hospitals were reported to the Ministry of Public Health, Thailand monthly. Each year 230 million OPD ICD-10 codes and 24 million IPD ICD-10 codes were sent to the Ministry for analysis and statistics production. Current ICD-10 coding in hospitals require a huge amount of work. Most of ICD-10 coding work were done by clinical coders in the hospital. However, the number of competent clinical coders in Thailand is not enough to supply all hospitals. So some hospitals assigned the ICD-10 coding job to some physicians or nurses which may produce many coding errors due to lack of knowledge in clinical coding rules. The automatic or semi-automatic ICD-10 coding system should be developed to replace the manual methods of ICD-10 coding in hospitals. In order to create the system, the diagnosis directory and algorithm to facilitate physician diagnosis mapping with concepts in ICD-10 must be developed first.